The issue of public sector information resources at the treshold of big data - Jacquinet, Marc (2021)
Jacquinet, Marc The Issue of Public Sector Information Resources at the Threshold of Bigdata,"Management Critique," in {https://critiquema.hypotheses.org}, 02/01/2017, https://critiquema.hypotheses.org/1309.